Probing Chemical and Mechanical Nanodomains in Copolymer Nanorods with Correlative Atomic Force Microscopy—Nano‐correscopy. (3rd April 2018) - Khanal, Dipesh; Zhang, Bokai; Ramzan, Iqbal; Marcott, Curtis; Li, Quan; Chrzanowski, Wojciech
Abstract: The interplay between size, shape, mechanical properties, and surface chemistry of nanoparticles orchestrates cellular internalization, toxicity, circulation time, and biodistribution. Therefore, the safety of nanoparticles hinges on our ability to quantify nanoscale physicochemical characteristics. Current characterization tools, due to their limited resolution, are unable to map these properties correlatively at nanoscale. An innovative use of atomic force microscopy‐based techniques, namely nano‐correscopy, overcomes this limitation and offers multiprobe capability to map mechanical (viscous and elastic) and chemical domains of nanoparticles correlatively. The strengths of this approach are demonstrated using polymer composite nanorods: m‐PEG‐PLGA ((m‐PEG–methoxy‐poly (ethylene glycol)‐ b ‐poly (lactic‐ co ‐glycolic) acid). Precise distribution of PLGA (monomers of lactide and glycolide) and poly(ethylene glycol) (PEG) polymer across nanorods is identified. The hydrophobic lactide component is found predominantly at the apex, while hydrophilic glycolide and PEG assembled at the body of the nanorods and correlate with a gradient of nanomechanical properties. New knowledge of how both nanochemical domains and nanomechanical properties are distributed across the nanorod will allow elucidating the interactions of nanorods with the proteins and biomolecules in the future, which will directly influence the fate of nanorods in vivo and will guide new synthesis methods. Abstract : The nano‐correscopy approach integrates atomic force microscopy–infrared, Lorentz contact resonance spectroscopy, and molecular force probe spectroscopy to enable correlative probing of chemical and physical material properties at nanoscale resolution. Nano‐correscopy characterizes with ultrasensitivity and multiprobe capability that cumulatively provide new insights into material nanostructure beyond single point assays.